Numerical investigation of the edge profile in hot-rolling - Veale, John (Centre for Research in Computational and Applied Mechanics (CERECAM), 2016)
During the hot-rolling of aluminium ingot into sheet, the material elongates in the rolling direction as it is reduced vertically. The spread which occurs in the lateral direction during the multiple pass schedules used in industry is minimal. However, the deformation on these edges is important. During the initial passes a concave profile develops - the material near the surfaces spreads outward while the material at the centre moves inward. The concave profile can lead to defects in the final product; these are the 'roll over' of material from the edges to the top and bottom surfaces, the fold over of material in the centre of the edge, and the formation of vertical edge cracks. To remove these the edges are trimmed at the end of the process. Research work in this area was motivated by the possibility of identifying means of reducing the amount of material that needs to be trimmed. The objectives of this thesis are to develop techniques of simulating the rolling, and to use these to investigate the deformation mechanisms which lead to the concave edge profile. Models of the rolling were developed using the general purpose, non-linear finite element code ABAQUS. To reproduce the edge profiles accurately requires large three-dimensional models, for which the explicit dynamic method was found to be the most suitable. The results of the analyses were used to investigate the mechanisms which lead to the concave edge profile. In the roll-gap the work-load arches through the ingot; and for roll passes with small reductions a stress pattern occurs which leads to the concave edge profile. In this pattern the stresses of highest magnitude at the surfaces are compressive stresses in the vertical direction, while in the centre of the ingot they are orientated in the rolling direction and are tensile. Thus deformation occurs by vertical compression near the surfaces, and by stretching in the rolling direction at the centre. At the edges the material is not constrained laterally; and due to the Poisson effect, the material spreads outward near the surfaces, and moves inward at the centre. The effect of certain variables on the edge profile were investigated with the modelling. The friction between the work-rolls and the ingot was found to have significant influence on the amount of lateral surface spread. Work hardening, strain rate and temperature effects in the material lead to variations in the yield stress through the height of the ingot. These effects were included in the modelling and were found to affect the shape of the profile, but to a lesser extent than the friction.